Applying Fuzzy Analytic Hierarchy Process (FAHP) in Healthcare System - Ahmad Ameryoun; Rouhollah Zaboli; Ali Akbar Haghdoost; Tayebeh Mirzaei; Shahram Tofighi; Mohammad amin shamsi (International Journal of Medical Research and Review, 2014)
Background and Purpose: Managers are applying multi-criteria decision-making methods like analytic hierarchy process (AHP) during the recent two decades mostly due to their positive properties. Moreover, integration of Fuzzy logic and multi-criteria decision-making methods increases capabilities of these methods. This study evaluates the FAHP method in healthcare system.Method: In this study, a systematic search done by means of Fuzzy Analytic Hierarchy Process, FAHP keywords separately and along with the words medical decision making, healthcare, health and their Persian equivalent inside PubMed, GOOGLE SCHOLAR, PROQUEST, SCOPUS, CINAL, SID and Iran doc databases without time periods and just regarding input and output criteria.Findings: finally 15 articles studied among 127 extracted articles in which the most application of this method is in evaluation of quality service and positioning while the least application is in other fields of healthcare system.Conclusion: Although applying FAHP methods in healthcare system increased but it is still low in contrast to other fields which can be due to unfamiliarity of authorities and students of the system.